Nephrotic syndrome without kidney injury revealing intravascular large B cell lymphoma. Issue 6 (12th June 2019) - Pothen, Lucie; Aydin, Selda; Camboni, Alessandra; Hainaut, Philippe
Abstract : We describe the case of a 64-year-old woman admitted for fever of unknown origin, who developed nephrotic syndrome during hospitalisation and pulmonary infiltrates. Renal biopsy disclosed intracapillary glomerular invasion by intravascular large B cell lymphoma. Clinical and biological evolution was favourable after rituximab, cyclophosphamide, doxorubicine, vincristine and prednisone (R-CHOP) treatment and autologous stem cell transplant. Two years after diagnosis the patient was considered in remission.